Modelo de implementación en las Mipymes, clúster plásticos, del sistema de gestión ética y socialmente responsable (2013)
This article we have reference to the current situation analysis of micro, small and medium enterprises (Mipymes) in Colombia, relating the importance of these in its economy and global environment. A model is proposed and its implementation in these companies (cluster) according plastic SGE Management System: 21, which integrates quality, safety and the environment, based on ethics and social responsibility. By implementing this model was observed a trend toward improvement in the categories: competitiveness, productivity and credibility. The model has differentiators with integrated management systems (IMS) to include the condition, compliance with ethics and social responsibility in the internal and external processes.